(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1911)
In November 1780 a meeting was called at which the formation of the society was proposed, and from which we may date its existence. A royal charter was obtained in 1782, whereby the reigning monarch is declared to be the patron of the Society. The first meeting at the house was held in April 1781. A history of the house and its depiction on early maps is presented.